Perception of Self-Esteem among Nursing Students at Nobel Medical College Teaching Hospital - Neupane, Saraswata; Pokherel, Indira; Khatri, Suja; Jha, Nilam Kumari (Journal of Nobel Medical College, 2022)
Background: Self-esteem is the own judgment of a person about himself or herself and appreciation of his/her value. An individual with high self-esteem has many positive effects and benefits. It is suggested that self-esteem is one of the most influential factors in the occupational behaviors of nursing students. So, the aim of the study was to assess the perception of self-esteem among Nursing Students. Materials and Methods: A descriptive cross-sectional study was conducted among nursing students at Nobel Medical College Teaching Hospital, Biratnagar, Nepal. The study was started after acquiring approval from the Institutional Review Committee of Nobel Medical College. Data was collected in the classroom through a self-administered questionnaire using the standardized tool Rosenberg Self-Esteem Scale (RSE) from July2021 to November 2021.A total of 238 students were taken as a sample by using the non-probability census method. Data analysis was done by descriptive study. Results: A total of 238 students participated in this study 79.4 percent had high self -esteem and 21.6 percent had low self-esteem. There was a statistically significant association between perception of self-esteem with the age of respondents, Current nursing programme and current nursing education. Conclusion: The study concluded that the majority of the respondents had high self-esteem. Acquisition of skill, knowledge, independence and acquire social, cultural and emotional adjustment increase high self-esteem.